Comparison of Central Corneal Thickness in Type 2 Diabetic Patients Versus Healthy Subjects - Tehmina Jahangir, Sana Jahangir, Haroon Tayyab (Pakistan Journal of Ophthalmology, 2017)
PURPOSE To compare the mean central corneal thickness in type II diabetics and non diabetics. STUDY design Case Control Study. PLACE AND DURATION OF STUDY Department of Ophthalmology, Unit II, Jinnah Hospital Lahore. Study was carried out over a period of six months from 10-07-2011 to 09-01-2012. MATERIAL AND METHODS A total of 120 patients (60 in each group) were included in this study. These patients were divided into two groups A and B. Patients with type II DM were assigned in Group A and age matched controls were assigned in Group B. CCT was measured in both groups using Alcon OcuScanRxPPachymeter and average of 10 consecutive readings from each eye were recorded in micrometers. results Mean age of the patients in group-A was 57.9±10.4 and in group-B was 56.1±11.3 years. In this study, 35 patients (58.3%) and 37 patients (61.7) were male in group-A and B, respectively. In group-A 25 patients (41.7%) and in group-B 23 patients (38.3) were females. When comparison was made in terms of central corneal thickness, group-A (diabetics) showed mean CCT 567.53±15.37 µm and group-B (non-diabetics) mean CCT was 532.69±9.40 µm. Statistically significant difference was noted between two groups (P<0.001) CONCLUSION It is concluded that diabetic patients exhibit a greater statistically significant average central corneal thickness than non-diabetics. key words Diabetes mellitus, Central corneal thickness, Pachymetry, Glaucoma.